“Woman Surau” Maria Kubtiah’s Work in Building Punjung Island Aisyiah Organization 1946-1995: “Perempuan Surau” Kiprah Maria Kubtiah Dalam Membangun Organisasi Aisyiah Pulau Punjung 1946-1995 - Rezi Oktania; Fansuri Mursal, Irhas; Wita, Gusmira (Indonesian Journal of Islamic History and Culture, 2024)
This research aims to analyze development of surau which was originally a traditional educational institution, where Bumiputra children learn traditional norms, ethics, manners and the Islamic religion. In Minangkabau tradition, boys who have reached puberty are prohibited from sleeping in the Rumah Gadang. Traditional surau education was reformed into a madrasa at the beginning of the 20th century. Interestingly, on Punjung Island there is a surau driven by "women" which is the basis for the birth and development of the Aisyiah organization. The research method uses historical research methods consisting of four stages, namely: Heuristics, source criticism, interpretation and historiography. The results of the research reveal Maria Khubtiah's contribution to advancing Islamic religious education on Punjung Island from 1942-1995. Traditional surau education was reformed into a madrasa at the beginning of the 20th century. The surau underwent renewal to become a semi-modern educational model. Maria Kubtiah is a figure who utilizes the function of the Surau and the 'Aisyiyah Organization as a forum for the Islamic Education movement. Maria Kubtiah is recognized by the community as a figure mobilizing women and a religious education figure in the Punjung Island community. Maria Kubtiah also served as an educator at the Muhammadiyah School from 1946-1970. In establishing the 'Aisyiyah Girls' Dormitory, Maria Kubtiah was appointed as the first girls' dormitory supervisor in 1964-1965. After PRRI, Maria Kubtiah founded a school at the Jambak surau as an effort to provide an alternative educational platform because the community education situation was chaotic due to the PRRI upheaval. He continued to struggle through critical times and became Leader of the Aisyiah Punjung Island Branch from 1950-1995.